1999
DOI: 10.1111/j.1572-0241.1999.01161.x
|View full text |Cite
|
Sign up to set email alerts
|

Achalasia and Down's Syndrome: Coincidential Association Or Something Else?

Abstract: Achalasia is an uncommon esophageal motor disorder. It has been associated with other diseases such as Parkinson's disease and depressive disorders, but coincidence of achalasia and Down's syndrome is rare. We report five cases of achalasia in Down's syndrome patients seen in our institution. Two of the five cases were diagnosed at pediatric age. Respiratory symptoms and growth retardation were the main clinical manifestations in pediatric patients, whereas adult patients mainly complained of dysphagia. Taking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(10 citation statements)
references
References 21 publications
1
7
1
1
Order By: Relevance
“…There are increasing reports on EA in DS patients [1,3]. In our case, the manometry could not confirm EA and showed abnormal esophageal peristaltic contraction, suggesting that the diagnosis was esophageal motor disorder, although clinically and radiologically the patient was EA.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…There are increasing reports on EA in DS patients [1,3]. In our case, the manometry could not confirm EA and showed abnormal esophageal peristaltic contraction, suggesting that the diagnosis was esophageal motor disorder, although clinically and radiologically the patient was EA.…”
Section: Discussioncontrasting
confidence: 62%
“…In our case, the manometry could not confirm EA and showed abnormal esophageal peristaltic contraction, suggesting that the diagnosis was esophageal motor disorder, although clinically and radiologically the patient was EA. There are also increasing reports on association of DS and esophageal motility disorders other than EA [1,3,8], mentioning that the esophageal motility disorders may be primary or secondary to GER. Hillemeier et al…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to oropharyngeal problems, a higher prevalence of esophageal motor disorders, particularly abnormalities in esophageal peristalsis and lower esophageal sphincter function in people with DS, is widely reported in the literature [13][14][15][16][17][18]. In their comparative study of 58 DS adults and 38 adults without DS, Zarate et al [15] identified a higher prevalence of achalasia in the DS subjects, symptoms of which included dysphagia for solids and liquids, regurgitation, and chest pain.…”
Section: Eating Drinking and Swallowing In Downõs Syndromementioning
confidence: 92%
“…Symptoms may be subtle and whereas adult patients mainly present with dysphagia, the chief clinical features in children were respiratory symptoms and growth retardation [113].…”
Section: Down Syndrome and Achalasiamentioning
confidence: 99%